2019
DOI: 10.1039/c9ra01063g
|View full text |Cite
|
Sign up to set email alerts
|

Modified core–shell magnetic mesoporous zirconia nanoparticles formed through a facile “outside-to-inside” way for CT/MRI dual-modal imaging and magnetic targeting cancer chemotherapy

Abstract: Magnetic mesoporous zirconia nanoparticle was synthesized by producing multiple iron oxide cores inside the cavity of mesoporous ZrO2 hollow nanospheres and was used for CT/MRI dual-modal imaging and magnetic targeting chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…Such values are comparable with those of CT/MRI dual contrast agents in the literature. 37,38 It was worthy to note that the HU values of Gd(OH) 3 lay between 72 and 138 and these were between those of Gd/MgAl (73-107 HU) and Gd/MgGa (83-174 HU) in the same concentration range. The higher HU values of Gd(OH) 3 than that of Gd/MgAl could be easily explained by the composition; Gd(OH) 3 had more highatomic-number elements than Gd/MgAl in the same weight.…”
Section: Resultsmentioning
confidence: 88%
“…Such values are comparable with those of CT/MRI dual contrast agents in the literature. 37,38 It was worthy to note that the HU values of Gd(OH) 3 lay between 72 and 138 and these were between those of Gd/MgAl (73-107 HU) and Gd/MgGa (83-174 HU) in the same concentration range. The higher HU values of Gd(OH) 3 than that of Gd/MgAl could be easily explained by the composition; Gd(OH) 3 had more highatomic-number elements than Gd/MgAl in the same weight.…”
Section: Resultsmentioning
confidence: 88%
“…Aiming to solve such a problem, a zwitterion-coated exceedingly small SPIONs (∼3 nm inorganic cores and ∼1 nm ultrathin hydrophilic shell) exhibited a high T 1 contrast power. 188 Once a synthesis procedure often produces traditional core− shell MNPs (from inside to outside), most of them have only a single T 2 W MRI imaging capability, an innovative strategy for mesoporous core−shell structural Fe 3 O 4 /ZrO 2 (M-MZNs) was proposed, where hollow mesoporous nanospheres (displaying an intrinsic characteristic for both CT imaging and drug loading) were used as matrix shell and the magnetic cores where produced in the pores of such shell, 189 being shown that the proposed M-MZNs exhibited MRI/CT dualmodal in vivo imaging capability and proper physical targeting to cancerous sites. 190 It was also reported that organic nanocarriers decorated with folate and loaded with Fe 3 O 4 MNPs acting as diagnostic imaging contrast agents, and paclitaxel acting as antitumoral drug, 191 exhibited high targeting ability and prolonged retention in human FR-α(+) FR-MDA-MB-231 tumor tissues as well as a lower tumor volume (∼40%) compared with mice administered with Endorem.…”
Section: Applications: From the Known To The Unknownmentioning
confidence: 99%
“…These composites exhibited not only superior magnetic properties and CT/MR imaging ability but also high drug loading capacity. [488] Optical-MR Imaging Agents: Optical imaging is a technique which is based on the detection of the light. Fluorescent organic dyes, quantum dots, or upconversion NPs have been included in magnetic composites in order to act as effective multimodal probes.…”
Section: Magnetic Nanocomposites As Effective Agents For Multimodal I...mentioning
confidence: 99%
“…[537,538] Magnetic nanocomposites of multiple morphologies were used for image-guided therapy in which different drugs have been delivered and released in specific diseased areas. Magnetic core-shell morphologies, for example, with SiO 2 , [446,529,539,540] C, [541] ZrO 2 , [488] or GO [452] in the shell could encapsulate DOX for chemotherapy or brain-targeted HIV treatment (tenofovir disoproxil fumarate). [484] It has been proved that an external magnetic field improves the cellular uptake efficiency of silica-based nanocomposites.…”
Section: Magnetic Nanocomposites As Effective Therapeutic Agentsmentioning
confidence: 99%
See 1 more Smart Citation